Preconditioned ADMM with nonlinear operator constraint - Benning, Martin; Knoll, Florian; Schönlieb, Carola Bibiane; Valkonen, Tuomo (IFIP Advances in Information and Communication Technology, 2016)
We are presenting a modification of the well-known Alternating Direction Method of Multipliers (ADMM) algorithm with additional preconditioning that aims at solving convex optimisation problems with nonlinear operator constraints. Connections to the recently developed Nonlinear Primal-Dual Hybrid Gradient Method (NL-PDHGM) are presented, and the algorithm is demonstrated to handle the nonlinear inverse problem of parallel Magnetic Resonance Imaging (MRI).
CRIS-Team Scopus Importer:2021-08-17
Keywords: ADMM; Iterative Bregman method; Nonlinear inverse problems; Operator splitting; Parallel MRI; Primal-dual; Proximal point method